2019
DOI: 10.3390/ma12030395
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Copper from Water by Adsorption with Calcium-Alginate/Spent-Coffee-Grounds Composite Beads

Abstract: Calcium Alginate/Spent-Coffee-Grounds composite beads (CA-SCGs beads), which were made of two different proportions of alginate and spent-coffee-grounds (3:3 and 3:10), respectively, were used to adsorb Cu2+ in aqueous solution. These beads were compared with calcium alginate beads (CA beads) and spent-coffee-grounds (SCGs) in terms of adsorption capacity and rate of adsorption. The experiments were carried out at an initial pH of 4 at 30 °C with initial concentrations of Cu2+ from 10 ppm to 100 ppm. Equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…SCGs have been encapsulated before in CA in our previous study, showing greater adsorption capacity for Cu 2+ in water and improved kinetics than CA alone at concentrations between 10 to 100 ppm of copper at pH 4 and 30 • C [17]. In the previous study, the larger adsorption by CA-SCG beads in comparison to the CA beads was seen in the lower range of concentrations (10 to 30 ppm).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…SCGs have been encapsulated before in CA in our previous study, showing greater adsorption capacity for Cu 2+ in water and improved kinetics than CA alone at concentrations between 10 to 100 ppm of copper at pH 4 and 30 • C [17]. In the previous study, the larger adsorption by CA-SCG beads in comparison to the CA beads was seen in the lower range of concentrations (10 to 30 ppm).…”
Section: Introductionmentioning
confidence: 85%
“…The reported estimated equilibrium constants in their study were: K Cu = 649 kgL/mol 2 , K Cd = 172 kgL/mol 2 and K Ni = 30.8 kgL/mol 2 [46]. Our previous study with Cu 2+ showed a great improvement in the kinetics of adsorption by the CA-SCGs beads versus the CA beads, despite that the study was at pH of 4, with more protons competing with the metal for adsorption sites [17]. Nevertheless, the current study shows improvement in the kinetics of adsorption of Cd 2+ in CA-SCGs versus the CA beads, but did not show any improvement in the kinetics of adsorption of Ni 2+ in CA-SCGs versus the CA beads.…”
Section: Kinetic Experimentsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is worth noting that we are still a great distance from organ printing. Even though recent deposition and manufacturing systems permit us to develop structures similar to tissue in their composition, the progression of entirely functioning tissue is a much more significant step [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Limitations Advantages and Future Prospects Of Alg 3d Prmentioning
confidence: 99%
“…This newly synthesized nano-particle was found to be very suitable in heavy metals removal because it shows a higher adsorption rate of 0.700, 0.451, and 0.790 mg.mg -1 for copper, nickel, and aluminum respectively. Therefore, it establishes itself as a promising sorbent for heavy metals sorption (Khan et al, 2020;Torres-Caban et al, 2019).…”
Section: Magnetic Iron-oxide (Feo) Nanoparticlesmentioning
confidence: 99%